Spectral Features of a Multi-Periodical Metamaterials - Girich, A.; Kharchenko, A.; Tarapov, S. (My University, 2019)
We numerically investigate the spectral properties of multi-periodic metamaterials of various configurations (the planar double-periodic photonic crystal and the bulk double-periodic magnetophotonic crystal) in the frequency range 15-45 GHz. In the first part of this paper we describe investigation of structure of the planar double periodic photonic crystal (PDPPC) which consists of two planar photonic crystals with large and small periods. A PDPPC unit cell consists of a series-connected narrow and wide segments of a microstrip transmission line. In the second part of this paper we will discuss results of investigation of a double-periodic magnetophotonic crystal (DPMPC) which consists of 3 unit cells. Each cell consists of periodically located 9 dielectric layers of quartz and teflon. On the border of the cell there is one layer of ferrite. We showed that both for a PDPPC and for a DPMPC in the transmission spectrum of these structures under study, a number of features arise: namely, narrow transmission peaks caused by the superposition of two spectra (with large and small periods) are observed in the stop bands of the spectrum. Such features may further allow the creation of a narrow-band filter for several frequencies for both planar structures and bulk ones.
Keywords: multi-periodical metamaterial; planar photonic crystal; magnetophotonic crystal; transmission spectrum; pass band; stop band